The Amplitude of Diaphragm Compound Muscle Action Potential Correlates With Diaphragmatic Excursion on Ultrasound and Pulmonary Function After Supraclavicular Brachial Plexus Block - Bao, Xiuxia; Liu, Tao; Feng, Haorong; Zhu, Yeke; Wu, Yingying; Wang, Xianghe; Kang, Xianhui (Frontiers in Medicine, 2022)
Objective This prospective, double-blind, randomized study assessed (1) the associations between diaphragm compound muscle action potential (CMAP), hemidiaphragmatic excursion, and pulmonary function after supraclavicular brachial plexus block (SCBPB) and (2) diagnostic efficacy of pulmonary function for hemidiaphragmatic paralysis evidenced by diaphragm CMAP as an assessment of diaphragm strength was evaluated. Methods Eighty-six patients were scheduled for the removal of hardware after healing of a right upper limb fracture distal to the shoulder who were randomly assigned in a 1:1 ratio to two groups: Group A (diaphragmatic excursion), or Group B (pulmonary function). Phrenic nerve conduction studies (PNCSs), M-mode ultrasonography of the diaphragm, and pulmonary function tests (PFTs) were performed before and 30 min after SCBPB. PNCSs were used to determine the latency and amplitude of diaphragm CMAP. Ultrasonography of the diaphragm was performed with patients in a supine position using a low-frequency probe over the subcostal space at the midclavicular line. The diaphragmatic excursion was measured during quiet breathing and deep breathing. Pulmonary function, i.e., forced vital capacity (FVC), predicted value of FVC, and forced expiratory flow in the first second (FEV1), was measured with spirometry. Receiver Operating Characteristic (ROC) curve analysis was used to assess the diagnostic efficacy of pulmonary function for hemidiaphragmatic paralysis evidenced by diaphragm CMAP as an assessment of diaphragm strength. Results There were significant associations between the reduction in amplitude of diaphragm CMAP and reductions in diaphragmatic excursion during quiet breathing (r = 0.70, p < 0.01) and deep breathing (r = 0.63, p < 0.01) when expressed as a percentage of baseline values. There were significant associations between the reduction in amplitude of diaphragm CMAP and reductions in FVC (r = 0.67, p < 0.01), FVC% (r = 0.67, p < 0.01), and FEV1 (r = 0.62, p < 0.01), when expressed as percentage of baseline values. The area under the ROC curve for FVC was 0.86. A decrease of >8.4% in FVC compared to pre-block predicted hemidiaphragmatic paralysis (determined by diaphragm CMAP) with sensitivity and specificity of 79.2 and 100%, respectively. Conclusions The relative reduction in diaphragm CMAP amplitude after SCBPB was correlated with relative reductions in diaphragmatic excursion and pulmonary function. FVC has potential as a useful diagnostic indicator of hemidiaphragmatic paralysis, evidenced by diaphragm CMAP, after SCBPB. These data establish diaphragm CMAP as a direct and objective index of diaphragmatic paralysis after SCBPB.